Hotels and Restaurants in Hanoi. (HHà Nội : Thế giới, 1997)
This booklet is meant to introduce to you, dear readers, a number of hotels and restaurants in Hanoi.
Keywords: Hanoi; Hotels; Restaurants; Hotels and Restaurants -- Tourist; Hanoi -- Hotels and Restaurants